Coverage of Dorsal-Ulnar Hand Wounds with a Reverse Second Dorsal Metacarpal Artery Flap - Zhang, Xu; Shao, Xinzhong; Ren, Chunzhen; Wen, Sumin; Zhu, Hongwei; Sun, Jianxin (Journal of Reconstructive Microsurgery, 2012)
This article introduces the use of a modified reverse dorsal hand flap harvested from the radial portion of the dorsal hand and wrist and the distal portion of the dorsal forearm for reconstruction of a large defect involving the third to fifth metacarpophalangeal (MCP) joints and the proximal phalanges. From May 2005 to August 2008, a modified reverse dorsal hand flap was transferred in 12 hands in 12 patients (9 male and 3 female). The mean age at flap transfer was 34.2 years (range: 23 to 50 years) old. All flaps survived. At final follow-up (mean, 28 months; range: 25 to 32 months), the mean active range of motion arcs of the third, fourth, and fifth MCP joints were 85 degrees (range: 65 to 97 degrees), 84 degrees (range: 60 to 90 degrees), and 83 degrees (range: 58 to 94 degrees), respectively. Our technique is useful and reliable for coverage of a large defect involving the third to fifth MCP joints and the proximal phalanges.
Keywords: arterial network; distal cutaneous branch of the second dorsal metacarpal artery; modified reverse dorsal hand flap